Marijuana for Glaucoma: A Recipe for Disaster or Treatment? - Sun, Xiaoshen (Yale J Biol Med, 2015)
Marijuana has been shown to lower intraocular pressure (IOP) but with limited duration of action and numerous adverse effects. Use of marijuana to lower IOP as a means of glaucoma treatment would require frequent use throughout the day, leading to significant adverse effects, possible progression toward Cannabis Use Disorder (CUD), and/or withdrawal symptoms. The treatment of glaucoma based on the cannabis plant or drugs based on the cannabinoid molecule should be considered carefully before being prescribed. Considerations should include the adverse physical and psychological adverse effects, including substance abuse. Currently, the deleterious effects of marijuana outweigh the benefits of its IOP-lowering capacity in most glaucoma patients. Under extremely rare circumstances, a few categories of glaucoma patients may be potential candidates for treatment with medical marijuana. Further studies on alternate routes and more focused means of cannabinoid molecule delivery to the eye for glaucoma treatment are needed.